Constitutional reform and the quest for a West Indian hermeneutics. - MC INTOSH, Simeon C.R. (1997)
Uses the Terms of Reference of the Barbados Constitution Review Commission to offer a philosophical critique of constitutional reform in the Commonwealth Caribbean. Discusses such issues as the patriation of the constitution, the Caribbean's continued relationship with the British Monarchy, and the possible restructuring of parliament. Provides a prescription for re-writing the constitutional texts. Presents a case for a Caribbean Court of Appeal, on the premise that this is critical to Caribbean self-definition.